A Csontbrigád orosz fordításának tiszteletteljes kritikája - Marosi, Lajos (Studia Litteraria, 2020)
The paper introduces the criticism of the Russian translation of one of the popular novels of Rejtő, Skeletal Brigade. Demonstrating through numerous examples and by the “backwards translation” of the Russian text, the author sets out to understand through certain instances what might have caused the spectacular mistranslations in the Russian text. The article may also serve as an example for the lack of similar thorough translation criticism in Hungarian critical literature, which might contribute to the improvement of the Hungarian literature translation.